Pengaruh Kemandirian Dan Dukungan Keluarga Terhadap Kewirausahaan Wanita Dengan Pendidikan Sebagai Variabel Moderating - Fadillah Saputri; Ani Murwani Muhar; Pitono Pitono (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
This study aims to determine the independence and family support for women's entrepreneurship with education as a moderating variable on women's entrepreneurship in Medan Denai District and Medan Area. The research design of moderated regression analysis was used as an analytical tool to determine how the influence between the independent and dependent variables was moderated by the moderating variable. This research uses associative research with a quantitative approach. The population and samples used in this study, namely female entrepreneurship in the Medan Denai District and Medan Area with a sample of 100 female entrepreneurship. The results of this study indicate that the variables of independence and family support have a significant effect on women's entrepreneurship. The education variable is able to moderate the influence of independence and family support significantly on women's entrepreneurship.